Advances in Visual Computing
DOI: 10.1007/978-3-540-76856-2_54
|View full text |Cite
|
Sign up to set email alerts
|

On Shape-Mediated Enrolment in Ear Biometrics

Abstract: Abstract. Ears are a new biometric with major advantage in that they appear to maintain their shape with increased age. Any automatic biometric system needs enrolment to extract the target area from the background. In ear biometrics the inputs are often human head profile images. Furthermore ear biometrics is concerned with the effects of partial occlusion mostly caused by hair and earrings. We propose an ear enrolment algorithm based on finding the elliptical shape of the ear using a Hough Transform (HT) accr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
2

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 8 publications
3
38
0
2
Order By: Relevance
“…A tracking method, which combined both skin-color model and intensity contour information, was proposed by Yuan and Mu [14] to detect and track the ear in sequence frames. Another ear detection technique is based on finding the elliptical shape of the ear using a Hough Transform (HT) accruing tolerance to noise and occlusion [15]. In [16], Cummings et al utilized the image ray transform to detect ears.…”
Section: Ear Detectionmentioning
confidence: 99%
“…A tracking method, which combined both skin-color model and intensity contour information, was proposed by Yuan and Mu [14] to detect and track the ear in sequence frames. Another ear detection technique is based on finding the elliptical shape of the ear using a Hough Transform (HT) accruing tolerance to noise and occlusion [15]. In [16], Cummings et al utilized the image ray transform to detect ears.…”
Section: Ear Detectionmentioning
confidence: 99%
“…They are designed to highlight specific properties of the outer ear, which occur in each image where the ear is visible no matter in which pose the ear has been photographed. In [38] the Hough transform is used for enhancing regions with a high density of edges. In head profile images, a high density of edges especially occurs in the ear region (see Figure 6(a)).…”
Section: Ear Detectionmentioning
confidence: 99%
“…In head profile images, a high density of edges especially occurs in the ear region (see Figure 6(a)). In [38] it is reported that the Hough transform based ear detection gets trapped when people wear glasses since the frame introduces additional edges to the image. This especially occurs in the eye and nose region.…”
Section: Ear Detectionmentioning
confidence: 99%
“…The second technique applied the algorithm described by Arbab-Zavar [10] to register the ear automatically, using the outer ear ellipse. In both cases the intensity values had their mean and standard deviation normalised.…”
Section: Comparison Implementationsmentioning
confidence: 99%
“…Arbab-Zavar et al [10] have proposed an enrolment technique exploiting the elliptical shape of the outer ear. This has produced good results with occlusion, but the accuracy of registration is much less than can be achieved manually.…”
Section: Introductionmentioning
confidence: 99%